Oestrogenic activity of mimosine on MCF‐7 breast cancer cell line through the ERα‐mediated pathway - Huq, AKM Moyeenul; Wai, Lam Kok; Rullah, Kamal; Mohd Aluwi, Mohd Fadhlizil Fasihi; Stanslas, Johnson; Jamal, Jamia Azdina (Wiley Online Library, 2019)
Hormone replacement therapy has been a conventional treatment for postmenopausal symptoms in women. However, it has potential risks of breast and endometrial cancers. The aim of this study was to evaluate the oestrogenicity of a plant‐based compound, mimosine, in MCF‐7 cells by in silico model. Cell viability and proliferation, ERα‐SRC1 coactivator activity and expression of specific ERα‐dependent marker TFF1 and PGR genes were evaluated. Binding modes of 17β‐oestradiol and mimosine at the ERα ligand binding domain were compared using docking and molecular dynamics simulation experiments followed by binding interaction free energy calculation with molecular mechanics/Poisson–Boltzmann surface area. Mimosine showed increased cellular viability (64,450 cells/ml) at 0.1 μM with significant cell proliferation (120.5%) compared to 17β‐oestradiol (135.2%). ER antagonist tamoxifen significantly reduced proliferative activity mediated by mimosine (49.9%). Mimosine at 1 μM showed the highest ERα binding activity through increased SRC1 recruitment at 186.9%. It expressed TFF1 (11.1‐fold at 0.1 μM) and PGR (13.9‐fold at 0.01 μM) genes. ERα‐mimosine binding energy was −49.9 kJ/mol, and it interacted with Thr347, Gly521 and His524 of ERα‐LBD. The results suggested that mimosine has oestrogenic activity.